Sleep, energy disturbances and pre-competitive stress in female traveller athletes - Silva, Maria-Raquel G.; Paiva, Teresa (Sleep Science, 2019)
Background: Gymnasts of high performance level are submitted to a demanding competitive schedule, which can negatively affect their circadian rhythm, sleep, appetite and pre-competitive stress. Therefore, the purpose of this study was to investigate sleep, body composition, pre-competitive stress and energy in elite female athletes just before a World Cup and potential sleep risks according to the travelled distance by athletes in order to compete.Methods: Sixty-seven rhythmic gymnasts of high performance level were evaluated in order to collect training and competition data, daytime sleepiness (DS) by the Epworth Sleepiness Scale, sleep quality (SQ) by the Pittsburgh Sleep Quality Index, precompetitive anxiety by the Sport Competition Anxiety Test-A and dietary intake prior to a World Cup.Results: Gymnasts suffering from severe DS had worse scores in the competition than those who reported normal DS (p=0.004). In addition, gymnasts with severe DS reported reduced SQ (p=0.014) and showed high levels of precompetitive stress (p<0.01). Gymnasts with reduced SQ demonstrated great DS (p=0.014) and high levels of precompetitive stress (p=0.010).Conclusions: Gymnasts demonstrated disordered sleep and precompetitive stress. Athletes who travelled long distances to compete presented high risk for short sleep duration, abnormal DS and reduced SQ.
Keywords: Sleep; Stress, Psychological; Energy; Athlete; Travel